COMPARISON OF THE DEFORMATION CHARACTERISTICS OF LOWWALL ON PIT C2 AND PIT 7 WEST BASED ON RADAR MONITORING DATA â PT BERAU COAL - Melistia Akhmadi, Nurbaiti
PT Berau Coal is a coal mining company located in Berau, East Kalimantan. The mining method used is open pit that closely related to excavation and stockpiling so it forms the slope of the mine, taking into economics and safety factors that require optimum mine slope design. Mining optimization is needed at PT Berau Coal to increase coal production, so mining beside the Life of Mine is carried out by real time slope monitoring and early warning system using radar monitoring, namely Slope Stability Radar (SSR). So that it can be determined the deformation characteristics of the slope instability, because the rock mass before the landslide will give a sign such as movement from deformation, velocity and invers velocity graph on SSR Viewer. Therefore, it is necessary to analyze the differences in the characteristics of the landslide that occur in two different pits so it can handling of mining operations before and after landslide happened. In this final assignment, the research was carried out at Lowwall Pit 7 West Site Binungan 2 and Pit C2 Site Sambarata where both slopes were monitored using SSR and happened Plane Failure, using SSR Viewer we can determine the deformation, velocity and inverse velocity so we can determine the deformation trend of each lowwall slope. The trend of movement on both slopes tends to be similar, namely linear – progressive – on set of failure – regressive – linear. However, there are differences in the characterictics of the two failure that occur. The difference that happen in both failure is caused by several factors that affect rain intensity, slope geometry, interlamination layer and material properties of weak planes.